ANALISIS SELISIH TARIF RUMAH SAKIT DENGAN TARIF INACBG’S PASIEN JKN RAWAT INAP KELAS 3 DAN KAITANNTA DENGAN KUALITAS PELAYANAN (Case Study pada RS Betha Medika - Sofian, Suci Rahmawati; Iskandar, Deni; Nurodin, Idang (Universitas Nusantara PGRI Kediri, 2020)
The aim of this study is to analyze differences in hospital rates and INACBG rates on the payment of claims for inpatient JKN class 3 patients and their relation to service quality.Data collected through observation, interviews, and documentation. The study used a descriptive qualitative method.The results of this study indicate that there are differences in hospital real rates with INACBG package rates. Of the 153 cases of disease, there was a positive difference received by the hospital, namely in the case of specialist internal medicine, surgical specialist, pediatric specialist, neurological specialist, and obgyn or midwifery